Clinician Perspectives on Managing Chronic Pain After Curative-Intent Cancer Treatment. Issue 4 (3rd April 2023) - Check, Devon K.; Jones, Katie F.; Fish, Laura J.; Dinan, Michaela A.; Dunbar, T. Kayla; Farley, Samantha; Ma, Jessica; Merlin, Jessica S.; O'Regan, Amy; Oeffinger, Kevin C.
Abstract : PURPOSE: Among cancer survivors who have completed curative-intent treatment, the high prevalence and adverse consequences of chronic pain are well documented. Yet, research on clinicians' experiences with and perspectives on managing chronic pain among cancer survivors is critically lacking. METHODS: We conducted semistructured interviews with 17 clinicians (six oncology, three palliative care, and eight primary care) affiliated with an academic medical center. Interview questions addressed clinicians' experiences with and perspectives on managing chronic pain (with or without opioid therapy) during the transition from active treatment to survivorship. A multidisciplinary team conducted content analysis of interview transcripts to identify and refine themes related to current practices and challenges in managing chronic pain in this context. RESULTS: Overall, clinicians perceived chronic pain to be relatively uncommon among cancer survivors. Identified challenges included a lack of clarity about which clinician (or clinicians) are best positioned to manage chronic pain among cancer survivors, and (relatedly) complexities introduced by long-term opioid management, with many clinicians describing this practice as outside their skill set. Additionally, although most clinicians recognized chronic pain as a biopsychosocial phenomenon, they described challenges with effectively managing psychosocial stressors, including difficulty accessing mental or behavioral health services for cancer survivors. CONCLUSION: Discovered challenges highlight unmet needs related to cancer survivor-clinician communication about chronic pain and the absence of a chronic pain management home for cancer survivors, including those requiring long-term opioid therapy. Research evaluating routine pain monitoring and accessible, tailored models of multimodal pain care in survivorship may help to address these challenges.